PENGARUH PERILAKU KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SLTPN KOTA BANDUNG - Hasanah, Aas (2013)
The purpose of this research is to find out an effect of the headmaster leadership on teacher's performance. This research is done trough the sample from the population of govemment junior high schools in Bandung. Some theories used as the research foundation are especially the headmaster leadership, including a leadership style, a headmaster 's role as an instructor, a manager, an administrator and supervisor, in connection with the development of the teacher 's performance. This research uses a quantitative approach with a descriptive method. The data collected through questionnaires, are processed by a computer trough SPSS and Excel Program, with the regression equation formula and then they are interpreted, analyzed and described based on the purpose of this research. The result of the regression linearity observation and data analysis obtained from the six hypotheses are the linear regression population. It is because the finding of the significant F at alpha -- 0.05. And the results show that the six working hypotheses are all accepted. It is supported b empirical data by obtaining the positive coefficient of correlation. Therefore, it can be interpreted that the headmaster leadership, including the leadership style, the headmaster 's role as an administrator, and the headmaster's role as a supervisor, both separately and together, has an effect on the teacher 's performance. From the research result, it can be concluded that (1). The style of the headmaster leadership has a huge positive effect on the performance of govemment junior high school teachers in Bandung; (2). The headmaster's role as a manager has an adequate positive effect on the performance of govemment junior high school teachers in Bandung; (3). The headmaster's role in administrator has a big positive effect on the performance of govemment junior high school teachers in Bandung; (4). The headmaster 's role as a supervisor has a big positive effect on the performance of govemment junior high school teachers in Bandung; (5). The headmaster's leadership, which consists of the leadership style, the headmaster as an instructor, a manager, an administrator, and a supervisor has a big positive effect on the performance of govemment junior high school teachers in Bandung. It is therefore recommended to many parties or institution to develop the headmaster leadership professionally in connection with the development of teacher's performance in order to develop education qualities in govemment junior high school in Bandung.